PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENGATASI KRISIS PANGAN DI YAMAN - Gemala Asyura; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes the role of the World Food Program (WFP) in overcoming the food crisis in Yemen. This research is interesting to discuss because the food crisis in Yemen is very bad and ongoing. WFP as an international organization came down to help Yemen which is one of WFP’s members. This study aims to find out what WFP is doing to help overcome the food crisis. This research is a qualitative research by collecting data through document analysis techniques. The theory used in this research is the theory of roles and functions of international organizations. This study uses the level of international system analysis to emphasize that the international system influences state behavior. The existence of international organizations is needed by the state to help them face the problems they have. The results of this study indicate that as an effort to overcome the food crisis in Yemen, WFP has implemented an Emergency Operation (EMOP) food assistance program to help the people of Yemen in a downturn in food crisis. WFP helps Yemen to be able to meet the daily food needs of its citizens with baskets containing food which are distributed regularly, there are also vouchers that can be exchanged for food that has been provided by WFP from suppliers who also work with WFP and help improve children's nutrition in Yemen by supplying special nutritious food for children in school and nursing mothers. In addition, WFP is also a means of channeling other countries that wish to provide assistance. Keywords: Food crisis, international organization, Yemen, WFP